Competing logics in the expansion of public service corporations. (June 2016) - Argento, Daniela; Culasso, Francesca; Truant, Elisa
Abstract: This paper contributes to the current debate on the evolving nature and meaning of public service corporations. It draws upon notions of neo-institutional theory and adopts a case study methodology. The study focuses on the case of SMAT, an Italian water corporation, whose value has been recognized at home and internationally. Findings show how a public service corporation's priorities and activities, particularly commercialization and internationalization, are constrained by various factors. These include: the burden of regulatory frameworks, the public nature of the corporation and its governance, the expectations of users, and the need for infrastructural investment. Highlights: A public service corporation's priorities and activities are constrained by external and internal factors. A public service corporation facing institutional complexity tends to adjust to the prevailing logics and expectations. A public service corporation may postpone commercialization and internationalization if major pressures work against them.